2021
DOI: 10.1590/0102-311x00081320
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with body mass index changes among older adults: a ten-year follow-up

Abstract: To examine changes in body mass index (BMI) among older Brazilian adults and associated factors. Longitudinal, population-based study, conducted in São Paulo, Brazil. Adults aged 60 years or over (n = 1,796) from the first wave of data collection from the Health, Well-Being, and Aging Study (SABE Project) conducted from 2000 to 2010. Repeated mixed-effects linear regression was used to analyze longitudinal changes in BMI and to examine whether sociodemographic characteristics, health conditions, and social beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(45 reference statements)
0
2
0
2
Order By: Relevance
“…Neste estudo, as mulheres solteiras/viúvas/divorciadas apresentaram maior chance de baixo peso do que as casadas, enquanto os homens solteiros/viúvos/divorciados apresentaram menor chance de excesso de peso. Dados do estudo Saúde, Bem-Estar e Envelhecimento (SABE), conduzido no Município de São Paulo, demonstraram que pessoas casadas de ambos os sexos, com 70 anos ou mais, tinham IMC mais elevado do que as solteiras 48 . Um estudo realizado com adultos (≥ 30 anos) também comprovou maior chance de sobrepeso e obesidade entre os participantes que viviam com companheiro 49 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Neste estudo, as mulheres solteiras/viúvas/divorciadas apresentaram maior chance de baixo peso do que as casadas, enquanto os homens solteiros/viúvos/divorciados apresentaram menor chance de excesso de peso. Dados do estudo Saúde, Bem-Estar e Envelhecimento (SABE), conduzido no Município de São Paulo, demonstraram que pessoas casadas de ambos os sexos, com 70 anos ou mais, tinham IMC mais elevado do que as solteiras 48 . Um estudo realizado com adultos (≥ 30 anos) também comprovou maior chance de sobrepeso e obesidade entre os participantes que viviam com companheiro 49 .…”
Section: Discussionunclassified
“…É provável que os adultos mais velhos que vivem sem companheiro estejam mais vulneráveis aos desvios nutricionais do IMC, seja baixo peso ou excesso de peso. O matrimônio ocasiona mudanças no estilo de vida e na assistência de atividades diárias, como a aquisição e preparo dos alimentos, e até nos próprios hábitos alimentares, afetando o peso corporal 10 , 48 , 49 de maneira diferente entre os sexos.…”
Section: Discussionunclassified
“…In a recent 15-year follow-up study, the authors reported that body weight stabilized up to the age of 65 and started to decrease after the age of 66 [ 25 ]. In another study carried out with the first three waves of the SABE study, which had a 10-year follow-up, a decrease in body weight was observed after the age of 70 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These types of foods may be particularly attractive to older adults, who often face challenges in purchasing and preparing food [ 29 ]. Furthermore, the modernization of lifestyles results in reduced physical activity, further contributing to the increase in body weight [ 26 ].…”
Section: Discussionmentioning
confidence: 99%